FAN ACTIVISM: MANIFESTASI AKTIVISME FANDOM DALAM GERAKAN KEADILAN IKLIM - Sari, Ida Ayu Gede Udyana; Dwita Apriani, Kadek; Putra Erawan, I Ketut (Jurnal Nawala Politika, 2023)
The research entitled “Fan Activism: Manifestations of Fandom Activism in the Climate Justice Movement” seeks to examine the understanding and strategies of the Kpop4planet movement from 2021 to 2022 in a qualitative descriptive way. Based on research with Henry Jenkins' perspective on fan activism, it seeks to analyze how fan activism is built within this movement. Fandoms offer a space to network, gather knowledge, and practice skills that can later be used for political change. This study reveals that the Kpop4planet movement is a global climate justice movement that calls on the K-pop industry in South Korea to take climate action. The movement is an embodiment of how fan activism is turned on and K-pop music fans as a force for climate justice change, and in general exemplifies what alternative political culture can be. Mobilization around the fandom occurs, fandom develops a grassroots communication system so as to create a communication network that expands the scale and speed of fan interaction, enabling a rapid and global response to evolving conditions.